IMPLEMENTASI KEBIJAKAN PEMUTAKHIRAN ADMINISTRASI PEMILIH DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR - Juliansyah, Elvi (Jurnal Ilmu Administrasi Negara, 2014)
Implementation of administrative policy updates voters in the election forgovernor and vice governor. This reseacrh aims to determine the administrative policyimplementation and updating of voter lists of data by the Voting Committee (VC)during the General Election of Governor and Deputy Governor of West Kalimantan in2007. This study used qualitative methods, the research instruments and procedures fordata collection using interviews, observation, and documentary. Subjects wereorganizers of the elections for governor and vice governor from regional electoralcommission (REC) until the voting committee (VC). The result of the research showedthat the implementation of the policy update data administration and voter lists had notbeen effective. The occurrence of the double voters and the swelling number of voters atsome polling stations (PS). The data base used in determining population provisionalvoters list (PVL) inaccurate and lack of coordination of the parties involved in theprocess of updating the data and voter lists.Key words:Policy implementation, data updating process, election of Governor andDeputy Governor. coordination